(untitled) (Raparin Journal of Humanities (RJH), 2026)
This research, entitled Culture as a Soft Power in Romanisation Policy (64 BC–138 AD), is a historical-analytic study that focuses on the use of culture as a soft power in Roman policies. In contrast to the commonly held belief that Rome had always depended mainly on the use of force, or "hard power", the research attempts to offer a new understanding on the strategy and policy of dominance of the Roman state through the application of the "soft power" theory. In terms of foreign policy, we assume that the Romans used cultural appeal as soft power in addition to economic hegemony and military conquest to establish their dominance over the conquered peoples and annexed lands. Based on the historical-analytical approach, the study aims to demonstrate how Roman rulers employed cultural elements such as urbanisation, theatre and public baths alongside other strategies and as part of foreign policy to consolidate their authority without relying regularly on military force. Overall, the study demonstrates that cultural policy was a successful instrument of power in Roman policy and comes to the conclusion that these cultural institutions were successful in diminishing protests, integration and social interactions, and establishing central authority without the use of power.